Optimization and Performance Evaluation of Foam Discharge Agent for Deep Aquatic Condensate Gas Well - Ge, Lei; Cui, Hailin; Li, Yingchao; Sui, Xiuan (Frontiers in Physics, 2022)
Block deep condensate gas reservoir in the basin in the southeast of the south China sea a for bottom water reservoir and production in the late effusion, production flow security problems such as scaling, within the wellbore fluid for condensate oil and water two phase, and subsea wellhead temperature is low, the mud line for this kind of gas well mud line high condensate content in low temperature, downhole high temperature, and the late bubble row agent and antiscale agent with features such as injection, The optimization and performance evaluation of foaming agent dynamic liquid carrying experiment was carried out. The experimental results show that the optimized foaming agent ZHY-01 has good resistance to high temperature and condensate oil, and the optimal concentration of foaming agent is recommended to be 0.25%. Under this concentration, the liquid carrying capacity of foaming agent decreases slightly by 10.17% at low temperature. MA/AA reduced the liquid carrying capacity by 11.86%, and PESA reduced the liquid carrying capacity by 10.17%. The results of this study can be used as a reference for the optimization of foam drainage agents in other well areas.